2019
DOI: 10.3390/a12110224
|View full text |Cite
|
Sign up to set email alerts
|

A QUBO Model for the Traveling Salesman Problem with Time Windows

Abstract: This work focuses on expressing the TSP with Time Windows (TSPTW for short) as a quadratic unconstrained binary optimization (QUBO) problem. The time windows impose time constraints that a feasible solution must satisfy. These take the form of inequality constraints, which are known to be particularly difficult to articulate within the QUBO framework. This is, we believe, the first time this major obstacle is overcome and the TSPTW is cast in the QUBO formulation. We have every reason to anticipate that this d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 62 publications
(108 reference statements)
0
42
0
2
Order By: Relevance
“…Essa estratégia consiste em dividirmos um problema de caixeiro viajante em subproblemas e depois conectar esses subproblemas como se fossem um núcleos e tratar esses núcleos como um outro caixeiro viajante. As referências [52][53][54] mostram o uso do computador quântico para resolver problemas deste tipo.…”
Section: Problema Do Caixeiro Viajanteunclassified
“…Essa estratégia consiste em dividirmos um problema de caixeiro viajante em subproblemas e depois conectar esses subproblemas como se fossem um núcleos e tratar esses núcleos como um outro caixeiro viajante. As referências [52][53][54] mostram o uso do computador quântico para resolver problemas deste tipo.…”
Section: Problema Do Caixeiro Viajanteunclassified
“…TSP with time windows (TSPTW) is another popular variant of TSP, which restricts the salesman to visit each target location within a particular time window. Reviews of existing solutions for TSPTW can be found in [38]- [40] and the references therein.…”
Section: B Tsp/vrpmentioning
confidence: 99%
“…A thorough statistical and computational analysis on asymmetric, symmetric, and national TSP benchmarks from the well known TSPLIB benchmark library, was conducted in [47]. Very recently, Papalitsas et al parameterized the TSPTW into the QUBO (Quadratic Unconstrained Binary Optimization) model [48]. This last QUBO formulation enables TSPTW to run on a Quantum Annealer and is an important step towards the ultimate goal of running the TSPTW utilizing pure quantum optimization methods.…”
Section: The Travelling Salesman Problemmentioning
confidence: 99%